2020
DOI: 10.3855/jidc.12282
|View full text |Cite
|
Sign up to set email alerts
|

Soluble fibrinogen-like protein 2 in condyloma acuminatum lesions

Abstract: Introduction: An imbalance in type 1 (Th1) and type 2 (Th2) T helper cells is associated with the development and recurrence of condyloma acuminatum (CA); however, the mechanisms underlying this imbalance remain unknown. We investigated soluble fibrinogen-like protein 2 (sFGL2), which is an effector of regulatory T cells (Tregs), to determine its role in the Th1/Th2 imbalance of CA. Methodology: Lesion and blood samples were obtained from 30 CA patients, and these samples were compared with genital skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…CA is caused by human papillomavirus infection [ 7 , 8 ]. It often occurs in the anus and external genitalia.…”
Section: Discussionmentioning
confidence: 99%
“…CA is caused by human papillomavirus infection [ 7 , 8 ]. It often occurs in the anus and external genitalia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that FGL2 has immunosuppressive effects on adaptive immunity by inhibiting dendritic cell maturation, downregulating T cell function and inducing B cell apoptosis [ 27 ], and the present study found that it is associated with infiltration of neutrophils and NK cells in AD. FGL2 is mainly derived from regulatory T cells (Tregs), and it reduces the production of IFN-γ and IL-17 [ 13 , 28 ]. Whereas regulatory T cells have low expression in AD [ 19 , 29 ], IFN-γ and IL-17 are highly expressed in AD [ 19 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…C Correlation between FGL2 and infiltrating immune cells. AD, aortic dissection cells (Tregs), and it reduces the production of IFN-γ and IL-17 [13,28]. Whereas regulatory T cells have low expression in AD [19,29], IFN-γ and IL-17 are highly expressed in AD [19,30].…”
Section: Discussionmentioning
confidence: 99%
“…Кондиломы возникают в результате папилломавирусной инфекции (HPVI), выявляются на фоне эктопии в 1,9% случаев преимущественно в группе женщин до 35 лет. Различают экзофитные остроконечные кондиломы и эндофитные формы кондилом (плоские кондиломы) [174]. В плане малигнизации наибольшее значение имеют плоские кондиломы.…”
Section: диагностическое значение морфологических показателей сошм в ...unclassified